Attitude Realization in Omicron News Reporting: Appraisal in Critical Discourse Analysis - Fifi Indriyani; Susana Widyastuti (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2023)
News production is a discursive act and a value-laden process through which media reports social issues using various stances to articulate certain ideologies. However, how reporters construct their stance and relationship with their readers has yet to significantly be an object of systematic investigation. This study sheds some light on the attitude of The Jakarta Post towards the spread of Omicron to reveal the media’s stances and ideological positions, in which certain interests play a role in discourse production. The principles of appraisal system and Critical Discourse Analysis (CDA) were deployed to examine 25 news articles about Omicron. The results reveal how language construes attitude and enables writers to position themselves evaluatively in certain aspects. While politically it deploys attitudinal resources to portray its neutral position, economically The Jakarta Post discloses itself as a media that accommodates its plural readers to maximize advertising revenue and reading traffic. This ideological stance is interpreted in light of the socio-political dimension that shapes news reporting.